2015
DOI: 10.1177/1934578x1501001124
|View full text |Cite
|
Sign up to set email alerts
|

A New Trinor-guaiane Sesquiterpene from an Indonesian Soft Coral Anthelia sp

Abstract: A new trinor-guaiane sesquiterpene has been isolated from an Indonesian soft coral Anthelia sp. The planar structure, possessing an octahydroazulene skeleton, and relative stereochemistry were established by analyzing 1D and 2D NMR data, including NOE experiments. Its absolute stereochemistry was elucidated to be 1S, 4S, 7R, and 10R by comparing observed and calculated optical rotation values. The new compound showed weak cytotoxicity against NBT-T2 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Therefore, the current primary issues in marine conservation, such as the loss of biodiversity through over-exploitation and habitat degradation, can be overcome. Additional information can be found in the Supplementary Materials [95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146,147,148,149,150,151,152,153,154,…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the current primary issues in marine conservation, such as the loss of biodiversity through over-exploitation and habitat degradation, can be overcome. Additional information can be found in the Supplementary Materials [95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146,147,148,149,150,151,152,153,154,…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Hanif et al reported on a “new” compound with the same structure as claruviridin B ( 92 ) [ 268 ]. However, an overall comparison of the NMR data of the two compounds unexpectedly showed that the structures were different, indicating that the metabolite isolated by Hanif was a stereoisomer of compound 92 [ 267 ].…”
Section: Tri- Nor -Guaianes: 111213-tri- ...mentioning
confidence: 99%
“…However, an overall comparison of the NMR data of the two compounds unexpectedly showed that the structures were different, indicating that the metabolite isolated by Hanif was a stereoisomer of compound 92 [ 267 ]. This metabolite, whose stereochemistry has yet to be elucidated, was mildly cytotoxic against NBT-T2 rat bladder epithelial cells [ 268 ].…”
Section: Tri- Nor -Guaianes: 111213-tri- ...mentioning
confidence: 99%
“…Among them, cembrane and briarane skeletons comprise a majority of the known diterpenoids in soft corals globally [ 2 , 3 ]. To date, soft corals of the genus Anthelia , family Xeniidae, have been shown to contain one type of sesquiterpenoid [ 4 ], three types of diterpenoids (xenicane [ 5 ], dolabellane [ 6 ], a C 24 -acetoacetylated diterpenoid [ 7 , 8 ]), and one type of steroid [ 9 ] with cytotoxic activity against various cell lines [ 4 , 5 , 6 , 7 , 8 , 9 ]. Moreover, the dolabellane stolonidiol ( 4 ), was identified as a promising candidate against Alzheimer’s disease after its mode of action in HEK293 cells was determined [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the dolabellane stolonidiol ( 4 ), was identified as a promising candidate against Alzheimer’s disease after its mode of action in HEK293 cells was determined [ 10 ]. In our continuing study of metabolites of Indonesian Anthelia [ 4 , 6 ], we isolated known diterpenoids 3 – 8 and new dolabellanes, named sangiangols A ( 1 ) and B ( 2 ), the structures of which are the subject of this article.…”
Section: Introductionmentioning
confidence: 99%